Structured credit products : credit derivatives and synthetic securitisation - Choudhry, Moorad (Singapore : Wiley & Sons (Asia), 2010)
Structured Credit Products are one of today's fastest growing investment and risk management mechanisms, and a focus of innovation and creativity in the capital markets. The building blocks of these products are credit derivatives, which are among the most widely used products in finance. This book offers a succinct and focused description of the main credit derivative instruments, as well as the more complex products such as synthetic collateralised debt obligations.
pt. 1. Credit risk and credit derivative instruments -- pt. 2. Structured credit products and synthetic securitisation -- pt. 3. CD-R.
&#x000A
Includes CD-ROM at the back.
&#x000A
Includes bibliographical references and index.
oif 23/05/13
Loan
Keywords: Credit derivatives